Bioactive peptides and gut microbiota: Candidates for a novel strategy for reduction and control of neurodegenerative diseases. (February 2021) - Wu, Shujian; Bekhit, Alaa El-Din Ahmed; Wu, Qingping; Chen, Mengfei; Liao, Xiyu; Wang, Juan; Ding, Yu
Abstract: Background: Neurodegenerative diseases are debilitating conditions that diminish the quality of life and pose significant financial and social burdens. Therefore, strategies to relieve and control these diseases are urgently required, which will improve the quality of patients' lives. Dysbacteriosis of gut microbiota has been shown to be a key component of neurodegenerative disease etiology. The homeostasis of gut microbiota and the balance of reactive oxygen species (ROS) in the gut can be altered by bioactive peptides derived from food sources. Therefore, biopeptides that improve neurodegenerative diseases by regulating gut microbiota have received considerable attention. Scope and approach: The impact of gut microbiota on the brain through the gut-brain axis has been summarized. Additionally, the dual role of ROS in regulating the homeostasis of gut and gut microbiota and the function of bioactive peptides in ameliorating neurodegenerative diseases via the microbiota-gut-brain axis are discussed. Potential strategies for the production and modification of peptides to improve their bioactivity are also highlighted. Key findings and conclusions: Increasing evidence supports that the gut microbiota modulates neurodegenerative diseases. Bioactive peptides that modulate the gut microbiota can be used as novel and strategic molecules to control and reduce neurodegenerative diseases. The bioactivity of the peptides can be dramatically influenced by different production and modification strategies. Strategies for further development of functional foods to ameliorate neurodegenerative diseases by regulating the gut microbiota are available. Future work should focus on the bioavailability and interactions of bioactive peptides and their impact on neurodegenerative diseases. Highlights: Crosstalk exists between brain and gut microbiota via the gut-brain axis. ROS has a dual role in the regulation of gut and gut microbiota. Peptides modulate the ROS balance in the gut and the composition of gut microbiota. Peptides influence the brain via the microbiota-gut-brain axis. Strategies in the production and modification of peptides affect their bioactivity.